Preliminary phytochemical investigation on the steam-distilled oil of Tangelo (Citrus paradisi Macf x Citrus reticulata Blanco - Ramirez, Lina P. (Quezon City: College of Pharmacy, University of the Philippines, 1978.)
The fresh peel from the matured fruits of tangelo (Citrus paradise Macf. X Citrus reticulata Blanco) was steam-distilled using a cleavenger apparatus for oils lighter than water. The fresh peel was found to contain 2.5% essential oil. The physical and chemical properties of the oil were determined and the sample was subjected to thin layer chromatography and ultraviolet spectrophotometry.
The volatile oil obtained from the fresh peel of the matured fruits of tangelo is colorless and has a characteristic aromatic odor. The oil has the following physical characteristics: specific gravity = 0.8524; refractive index = 1.46948; optical rotation = -108.9873.
The components of the tangelo oil were isolated using thin layer chromatography and UV spectrophotometry. The tangelo oil gave a maximum absorbance in the wavelength of 212 nm.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, October 1978.
Keywords: Grapefruit; Mandarin orange; Tangelo; Tangerine; Pomelo